1988
DOI: 10.2307/2444194
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Leaf Variegation in Saintpaulia ionantha During In vitro Propagation and During Chimeral Separation of a Pinwheel Flowering Form

Abstract: Plants of the foliarly variegated cultivar Saintpaulia ionantha Tommie Lou and the florally variegated cultivar Candy Lou were regenerated through tissue culture from leaf sections, petal sections, and subepidermal tissue. This provided explants with derivatives of all histogen layers of the shoot apex, layers I and II only, and layers II and III only. Over 1,000 plants of Tommie Lou and Candy Lou were grown to flowering. A low level ofphenotypic variation was observed, but in no case could this be attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…All of their adventitious buds produced monochromatic pink flowers, indicating that only the epidermis layer contributed to adventitious bud ontogenesis in this cultivar (Yang et al, 2017 ). This type of chimera separation was consistent with many other studies (Naylor and Johnson, 1937 ; Broertjes et al, 1968 ; Broertjes and van Harten, 1985 ; Peary et al, 1988 ; Ohki, 1994 ; Lo, 1997 ; Hosokawa et al, 1998 ). On the other hand, we selected “Concord” and “Monique,” in which a true-to-type pinwheel can be propagated at a relatively high frequency even through adventitious shoot regeneration.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…All of their adventitious buds produced monochromatic pink flowers, indicating that only the epidermis layer contributed to adventitious bud ontogenesis in this cultivar (Yang et al, 2017 ). This type of chimera separation was consistent with many other studies (Naylor and Johnson, 1937 ; Broertjes et al, 1968 ; Broertjes and van Harten, 1985 ; Peary et al, 1988 ; Ohki, 1994 ; Lo, 1997 ; Hosokawa et al, 1998 ). On the other hand, we selected “Concord” and “Monique,” in which a true-to-type pinwheel can be propagated at a relatively high frequency even through adventitious shoot regeneration.…”
Section: Introductionsupporting
confidence: 90%
“…In general, adventitious shoot formation is thought to occur from a single cell in many plants (Broertjes et al, 1968 ; Broertjes and Keen, 1980 ; Abu-Qaoud et al, 1990 ). Histological observations at adventitious shoot formation from leaves in Saintpaulia also suggested that only their epidermal layer participates in new SAM formation (Naylor and Johnson, 1937 ; Broertjes et al, 1968 ; Broertjes and van Harten, 1985 ; Peary et al, 1988 ; Ohki, 1994 ; Lo, 1997 ; Hosokawa et al, 1998 ). SAM of this single layer originate adventitious buds that must be composed by a single genetic background, and thus their phenotypes often differ from the mother plant, whose SAM is composed by several genetically distinct cell layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have focused on the causes of these variations in response to tissue culture. Although some forms of variegation are caused by differences in genetic expression among genetically identical cells (Peary et al, 1988), others-eesult from chimerism where single plants are composed of genetically dissimilar cells (Marcotrigiano et al, 1990). The genetic basis of mutations altering pigment production has already been in-I Manuscript received I September 1995; revision accepted 21 March 1996.…”
mentioning
confidence: 99%
“…The colors of the petals ranged from red to white and pale pink to red petals edged with clear white lines. There have been some reports that cultivars with chimeral leaves are stable during culture periods, while the chimeral petals exhibited variation when regenerated (Lineberger and Druckenbrod, 1985;Peary et al, 1988). The leaf segments of the variants cultured in our study showed a number of variations, which could be affected by the chimera layers.…”
Section: Resultsmentioning
confidence: 49%